Associations between three diet quality indices, genetic risk and body composition: A prospective cohort study. Issue 9 (September 2022) - Livingstone, Katherine M.; Milte, Catherine; Bowe, Steven J.; Duckham, Rachel L.; Ward, Joey; Keske, Michelle A.; McEvoy, Mark; Brayner, Barbara; Abbott, Gavin
Summary: Background & aims: Diet and genetic predisposition to adiposity are independent predictors of body composition, yet few cohort studies have examined the association between overall diet quality indices, genetic risk and body composition. This study examined the prospective association of three diet quality indices and a polygenic risk score (PRS) with trunk fat mass, total fat mass, lean mass and bone mineral content. Methods: Adults from UK Biobank cohort were included. Dietary intake was assessed using the Oxford WebQ and three diet quality indices calculated: Recommended Food Score (RFS); Mediterranean Diet Score (MDS); Healthy Diet Indicator (HDI). Bioimpedance data were available for trunk fat, total fat and lean mass (kg). Trunk fat mass (kg), total fat mass (kg) and lean mass (kg) were assessed using bioelectrical impedance (BIA) in 17, 478 adults. Bone mineral content (g) was available from dual energy x-ray absorptiometry (DXA) scans in 11, 887 participants. Linear regression analyses, adjusted for demographic and lifestyle confounders, were used to estimate prospective associations between each diet quality index and body composition outcomes. A PRS created from 97 adiposity-related single nucleotide polymorphisms was used to examine interaction effects. Results: A total of 17, 478 adults (M = 55.9, SD 7.5 years) were followed up for up to 10 years. RFS, HDI and MDS were inversely associated with trunk fat (RFS: B −0.29; 95% CI: −0.33,  −0.25; HDI: −0.23; −0.27,  −0.19; MDS: −0.22; −0.26,  −0.18), total fat (RFS: B −0.49; 95% CI: −0.56,  −0.42; HDI: −0.38; −0.45,  −0.32; MDS: −0.38; −0.44,  −0.32) and lean (RFS: B −0.10; 95% CI: −0.14,  −0.06; HDI: −0.07; −0.11,  −0.03; MDS: −0.07; −0.11,  −0.04) mass. Diet quality was positively associated with bone mineral content (RFS: B 8.23; 95% CI: 2.14, 14.3; HDI: 6.77; 1.00, 12.5). There was evidence of non-linear associations between diet quality (RFS and HDI only) and trunk fat (p < 0.01) and total fat mass (p < 0.05). There was limited evidence PRS was associated with body composition, with interaction effects of PRS and HDI (p-interaction = 0.039) and MDS (p-interaction = 0.031) on total fat mass. Conclusion: Higher diet quality was associated with lower trunk fat, total fat and lean mass, regardless of the diet quality index examined (RFS, HDI or MDS), while higher diet quality (RFS and HDI only) was associated with higher bone mineral content. The benefit of higher diet quality on reducing total fat mass was most evident in individuals with higher generic risk of adiposity. These findings underscore the importance of a high-quality diet for maintaining optimal body composition, particularly in individuals with genetic pre-disposition to adiposity.